Tafsir Al-Mishbah in the Frame Work of Indonesian Golden Triangle Tafsirs: A Review on the Correlation Study (Munasabah) of Qurâan - Said, Hasani Ahmad (Center for Research and Development of Religious Literature and Heritage, 2014)
This study elaborates and puts M. Quraish Shihab and Tafsir al-Mishbah in the discourse of Indonesian exegesis (Tafsir). This paper also tries to place Tafsir al-Mishbah which is currently the most comprehensive interpretation among other Indonesian mufassirsâs work that have a complete interpretation. Further explanation on Tafsir al-Mishbah and other mufassirs are considered necessary, so that Tafsir al-Mishbah will have a clearer position in the academic world. Besides mapping and positioning Tafsir al-Mishbah among other Indonesian interpretations, this paper will also look in depth at the correlation of the study of the Al-Qur`an in the previous interpretations. The result of the study shows that the work of M. Quraish Shihab is the most serious interpretation elaborating the Quranic verses in detail and trying to seek the correlation among the verses or chapters (surah).